Technologies for implementing a mentoring model to facilitate the professional development of young teachers - Victoria V. Kandakova (Развитие образования, 2025)
The article addresses the current problem of the professional development of young teachers in the modern education system, characterized by rapid changes and high demands on teacher qualifications. The research aims to substantiate and test a set of effective technologies for implementing a mentoring model that promotes the successful adaptation and professional growth of young professionals. The article presents the results of a theoretical analysis of existing approaches to mentoring, systematizes modern technologies used in educational practice, and defines criteria for the effectiveness of these technologies. Particular attention is paid to the analysis of mentoring programs implemented in various regions. The article contains conclusions about the effectiveness of the developed mentoring model and recommendations for its implementation in educational institutions, including the need for clear criteria for selecting mentors, improving their qualifications, and an individual approach to each young specialist. It is emphasized that mentoring should be considered as a process of mutual enrichment and professional growth, creating a favorable environment for the development of pedagogical culture and improving the quality of education.